Phylogeny - Javernick, Michael, author; Dormer, James T., advisor; Orman, Jack L., advisor; Voss, Gary Wayne, committee member; Ruby, Christine, committee member (Colorado State University. Libraries, 1993)
My intention has been to synthesize and hybridize forms and marks into unique and compelling visual poetry. Having worked as a biologist in the past, I am intimately familiar with the structures and processes associated with living things. The language of shapes, forms and marks with which I have chosen to work is informed by this familiarity. The majority of the work is done in the media of intaglio prints because I felt the images required the tremendous complexity of marks for which this media allows. I approached the plates as sculpture, treating it as a relief surface. Every plate and corresponding image speaks of an intense, sometimes aggressive, physical involvement. Much of the actually image making occurred subtractively through either scraping or open-biting. Images where more "found" than "built". Drawing has provided me with the opportunity to more rapidly transform and search for images, and has made preliminary experimentation with color possible. All the works can be seen as descendants of the drawing Cloaca. The bilateral symmetry and kidney-like motif of this image have undergone transformations in each successive image. As these mutations compounded new motifs appeared. While the images do speak of the phenomena of organic life, my only conscious intention has been to create work that is visually intriguing and speaks of my unique and personal vision.
Keywords: Symbolism in art; Visual poetry